Overview of farming practices in the water-logged areas of Kerala, India - P R, Jayan; Sathyanathan, Nithya (International Journal of Agricultural and Biological Engineering, 2010)
Abstract: Water logging is one of the major problems of land degradation in India. Unscientific management of soil, water and crops in irrigated lands, and obstruction of natural drainage systems by various developmental activities are the main factors responsible for disrupting the balance of inflow and outflow of water, leading to water stagnation. While irrigation has increased by leaps and bounds, its attendant problem of water logging is now plaguing substantial area of agricultural lands. The low-lying areas of Kerala, the southernmost state of India, are potential areas of paddy production. But these areas are situated below the mean sea level and have serious problems of water-logging. About twenty five percent of total paddy lands in Kerala are water-logged; especially in Kuttanad, Pokkali, Kole and Kaipad areas. An integrated rice-shrimp/ prawn farming are practiced in these areas. One rice crop followed by shrimp/prawn capture provides a substantial subsidiary income to the farmer. The major issues faced in these areas are mainly related to pollution, eutrophication, encroachment, reclamation, mining and biodiversity loss. As a result of denuding, polluting, draining, filling, etc., these water-logged areas have been under severe threat. The potentiality of these areas should be exploited and necessary measures in conserving these areas need to be undertaken. Sustainable farming where a judicious mix of integrated enterprise concept of resource based planning based on public participation is slowly developing in these areas. A clear perspective and a management system that ensures participation and regulation in resource use are essential. Keywords: wetlands, ecosystems, India, water-logging, rice-shrimp farming, Kuttanad-Pokkali-Kole-Kaipad DOI: 10.3965/j.issn.1934-6344.2010.04.018-033 Citation: Jayan P R, Nithya Sathyanathan. Overview of farming practices in the water-logged areas of Kerala, India. Int J Agric & Biol Eng, 2010; 3(4): 18<span style="line-height: 130%; font-family: